The embattled bank regulator - Ogunleye, Ganiyu (Lagos, Nigeria Kachifo, 2018)
The book chronicles the author's experiences and the challenges he faced as Director of Banking Supervision at the Central Bank of Nigeria for seven years and as Managing Director of NDIC for ten years. He interrogates topical issues such as consequences of a liberal licensing regime, effectiveness of "fit and proper" persons test, use of capital entry barrier, implications of appointing commercial bankers as CBN governor, implications of court-ordered restoration of banking license and constraints to prompt discharge of deposit insurance liabilities.
Includes index
oif 17/12/2019
Loans
Keywords: Banks and banking---State supervision; Banks and banking--Government policy; Banking law